Die trying - Child, Lee (Child, Lee. Jack Reacher novel, 2005)
In a plot to overthrow the U.S. government, Montana neo-Nazis abduct the daughter of the nation's top general and her male companion. The companion is Jack Reacher, a former military policeman and he turns the tables on the captors.